2021
DOI: 10.1177/1069072721994272
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese Version of the Multidimensional Workaholism Scale

Abstract: The aim of this study was to translate the Multidimensional Workaholism Scale (MWS) into Chinese and then test its reliability and validity among full-time Chinese employees in two stages. In Study 1 ( N = 220), the MWS was translated and exploratory factor analysis was conducted resulting in a four-factor solution consistent with the original MWS: motivational, cognitive, emotional, and behavioral. In Study 2 ( N = 425), confirmatory factor analysis showed that a four-factor, bifactor model was the best fit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 45 publications
5
26
1
Order By: Relevance
“…The results revealed that the two-factor model has a better fit than the single-factor model (normalΔCFI .01, normalΔRMSEA > .015), which indicates that the two variables are related but are distinct concepts. As for job satisfaction, the MWS did not show a significant association with job satisfaction (r = .02, p > .05), consistent with previous studies (Clark et al, 2020; Xu & Li, 2021).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The results revealed that the two-factor model has a better fit than the single-factor model (normalΔCFI .01, normalΔRMSEA > .015), which indicates that the two variables are related but are distinct concepts. As for job satisfaction, the MWS did not show a significant association with job satisfaction (r = .02, p > .05), consistent with previous studies (Clark et al, 2020; Xu & Li, 2021).…”
Section: Resultssupporting
confidence: 90%
“…First, the Korean version of the MWS developed in Study 1 was used to measure workaholism. Similar to the results of Study 1 and previous research (αs range from .74 to .93; Clark et al, 2020; Xu & Li, 2021), the scale showed good internal consistency in the present study as well. The Cronbach’s alpha was .83 for the motivational, .91 for cognitive, .84 for emotional, and .90 for behavioral.…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…We created dichotomous categorical variables for conducting invariance tests for gender, age, education, and job position (Milfont and Fischer, 2010;Schoot et al, 2012). Similar to previous studies (Duffy et al, 2019;Xu and Li, 2021), our gender comparison was between men and women, and for age we used two groups: low (those whose response was ≤ mean age, 34.68) and high (those whose response was > mean age, 34.68). We split education level into two groups, undergraduate degree and below and master's degree or above; for job position, we compared front-line employees and managers.…”
Section: Discussionmentioning
confidence: 99%